God, I Can't Stop Thinking About Sex! The Rebound Effect in Unsuccessful Suppression of Sexual Thoughts Among Religious Adolescents. Issue 2 (12th February 2019) - Efrati, Yaniv
Abstract : The rebound effect of thought suppression refers to attempts to suppress thoughts that result in an increase of those thoughts. The aim of this three-study research was to investigate the suppression of thoughts and its possible importance in the cognitive model of predicted compulsive sexual behavior (CSB) among Israeli Jewish religious and secular adolescents. Study 1 ( N  = 661): Do religious and secular adolescents differ in CSB and related psychopathology? Study 2 ( N  = 522): Does CSB mediate the link between religiosity and well-being? Study 3 ( N  = 317): Does religiosity relate to suppression of sexual thoughts, which relates to higher CSB and lower well-being? The analyses indicated that religious adolescents are higher in CSB than secular ones, and that sexual suppression and CSB mediate the link between religiosity and well-being. Results are discussed and address the need for a broader understanding of CSB and the function of thought suppression.